Perspectives of Thai educators toward 21st century instruction - Veena Prachagool; Prasart Nuangchalerm (Intelektual Pustaka Media Utama, 2021)
The rapidly changed in our society and education may influence to nature of learning and learning behaviors in young new generation. The 21st century learning is requiring educators to prepare our children by quality of learning and teaching. Teachers are key change agent to help learners live and learn with new learning environments. The study aimed to explore perspective of Thai educators toward 21st century learning and teaching by surveying method. The study investigated 41,991 educators who have responsibility or concerns in teaching and learning. Data were collected through online questionnaire and then analyzed by statistical package in terms of frequency and percentage. Finding revealed that 21st century learning and teaching in classroom should be conducted in appropriate ways, but a few misunderstand in support system and learning environment were reported. Educators should be discussed and prepared both teachers and learners to modern classroom.